Correlation between Spirituality Levels and Stress among First-Year Students in Health Science Programs - Fitriani, Dwi Rahmah; Chairunnisa, Aldilla Asri; Asthiningsih, Ni Wayan Wiwin (Genius Journal, 2025)
Introduction: University students, particularly those in health-related programs, are often subjected to various academic demands that must be completed within strict timeframes. These demands, coupled with a lack of preparedness to cope, can lead to psychological issues such as stress. Globally, stress affects more than 350 million people and ranks as the fourth most common health problem. Objective: This study aimed to determine the relationship between spirituality levels and stress among freshmen in the Health Sciences Program at Universitas Muhammadiyah Kalimantan Timur. Methods: This research employed a quantitative approach with a cross-sectional design. A total of 271 respondents were selected using random sampling. The instruments used were the Daily Spiritual Experience Scale (DSES) to measure spirituality and the Depression Anxiety and Stress Scale (DASS-21) to measure stress levels. Data were analyzed using the Spearman rank correlation test. Results: The majority of respondents had a high level of spirituality (160 respondents or 59%), while most respondents also reported normal levels of stress (159 respondents or 58.7%). Statistical analysis revealed a negative correlation between spirituality and stress levels, with a correlation coefficient of -0.417 and a p-value of 0.000, indicating a significant inverse relationship. Conclusion: The findings indicate that higher levels of spirituality are associated with lower levels of stress among new health students. This suggests that spirituality may serve as a protective factor and should be considered in holistic student support and stress management programs in higher education settings.